Strengthening Patriotism to Prevent Terrorism: A Study on Muhammadiyah Pesantrens In South Sulawesi, Indonesia - Maryam, Maryam; Muhsin, Muh Arief; Samsuriadi, Samsuriadi (AL-ISHLAH: Jurnal Pendidikan, 2024)
The focus of the research aims to analize the role of Muhammadiyah Pesantrens in instilling the sense of patriotism for the prevention of terrorism. The study is designed with a qualitative setting using a phenomenological approach to understand individuals' experiences and perceptions of the concept of love for their homeland, and a constructivist approach to understand how pesantrens actively initiate and implement programs to strengthen such attitudes. The data collected through observation and interview. The findings of the research indicate several preventive measures taken by Muhammadiyah pesantrens in strengthening the love for the homeland to prevent the spread of terrorism seeds such as education moderate and progressive Islamic value, cultivation of national character, and teaching of understanding the danger of terrorism. These measures include embedding education with progressive moderate Islamic values. This is realized by developing a curriculum based on moderate, tolerant, and inclusive Islamic values. Moderate Islam is a humanistic Islam that can accommodate everyone, from various social strata, ethnicities, and religions; tolerance is a fundamental value in Islam; inclusive education is the educational service provided by Muhammadiyah pesantrens, which does not discriminate based on skin color, ethnicity, religion, race, or social group. Another step is the cultivation of national character among the santri, which involves reinforcing knowledge of local history and culture based on Al-Islam and Muhammadiyah principles. A relevant future study would be to investigate the causes of the emergence of anti-diversity attitudes and hardline Islam found in some pesantrens in Indonesia.